Microneedles Coated with Cow’s Milk Proteins: Immunogenicity, Stability, and Safety Assessment - Venkatesa Prabhu, Ghanesh Kesav; Shakya, Akhilesh Kumar; Gill, Harvinder Singh (Molecular pharmaceutics, 2025)
Cow’s milk allergy (CMA) is one of the most frequently occurring food allergies in children, especially in infants less than 3 years old. Mindful avoidance of CMA-triggering foods and prompt epinephrine injection to overcome anaphylaxis in the case of accidental ingestion are the only options currently available to allergic subjects. This study investigates the potential of coated microneedles for delivering CMA into the skin as a novel approach to allergen immunotherapy. Precise amounts of cow’s milk proteins (CMP) were dip-coated onto stainless steel microneedle patches and reproducibly delivered to mice epidermis and dermis. Microneedle delivery did not cause bleeding or visible erythema and did not induce skin alarmins, thymic stromal lymphopoietin (TSLP), and IL-33. Dose-dependent elevations in cow’s milk allergen-specific IgG, IgG1, and IgG2a levels were observed in Balb/c mice after three weekly microneedle immunizations. Microneedle immunizations proved to be as effective as subcutaneous immunizations without elevating undesired allergen-specific IgE. Moreover, microneedles could be stored at room temperature for at least three months without deterioration in coating integrity. Overall, these results suggest that coated microneedles are viable candidates for treating CMA, warranting further investigation.